Conhecimento de mães sobre promoção de saúde bucal em bebês - Santos, Karen Chritine [UNESP]|Monnazzi, Aline Critina Arone [UNESP]; Rosell, Fernanda Lopes [UNESP]; Silva, Silvio Rocha Corrêa da [UNESP]; Valsecki Júnior, Aylton [UNESP]; Tagliaferro, Elaine Pereira da Silva [UNESP] (My University, 2011)
The aim of this study was to assess the knowledge level on oral health promotion for babies of all mothers (n=60), aged 18-42 years, assisted in the Preventive Dentistry Clinic of the Faculty of Araraquara, at Universidade Estadual Paulista (UNESP), during the period 2005-2008. Methods - An interview was performed using a questionnaire with 18 open and five closed questions about knowledge and practices related to caries prevention as well as demographic information. Methods - The majority believed that breast milk does not cause caries (73,3%), that caries is not a transmissible disease (51,6%) and that anatibiotics cause caries (63,3%). Almost all mothers (93,3%) responded that brushing teeth could prevent the disease, action that should be initiated since first tooth erupts (75%). For 73,3% of the respondents, the use of dental floss should be initiated onle after all deciduous teeth erupt. Results - The majority (83,3%) knew what was fluoride, but a third of them (33,3%) did not know the best time to start using it. The dentist counseling related to oral health of babies was considered imoprtant by 96,7% of mothers. Conslusion - The mothers presented good knowledge about baby's oral hygiene, however, they did not know about other important variables for oral health promotin of babies.

O objetivo desse estudo foi avaliar o nível de conhecimento sobre promoção de saúde bucal em bebês de todas as mães (n=60), com idade de 18-42 ano, que frequentaram a Clínica de Prevenção da Faculdade de odontologia de Araraquara, da Universidade Estadual Paulista (FOA-UNESP), durante o período 2005-2008. Métodos - Realizou-se uma entrevista utilizando questionário contendo 18 questões abertas e cinco fechadas sobre o conhecimento e práticas em saúde bucal de bebês relacionadas à cárie e sua prevenção, bem como sobre informações sociodemográficas. Resultados - A marioria das mães acreditava que o leite materno não causa cárie (73,3%), que está mães (93,3%) responderam que a doença poderia ser evitada excovando os dentes, ação que deceria ser iniciada desde o nasciemnto do primeiro "dente de leite" (75%). Para 73,3% das entrevistadas, o uso do fio dental deveria ser iniciado somente após o irrompimento de todos os "dentes de leite". A maior porcentagem das mães (83,3) sabia o que era o flúor, mas 33,3% desconheciam a época ideal para iniciar sua utilização. A orientação do cirurgião-dentista em relação à saúde bucal de seus bebês foi considerada importante por 96,7% das mães. Convlusões - As mães entrevistadas demonstraram conhecimento em relação à escovação dental em bebês, como os fatores etiológicos da doença, uso de compostos fluoretado e visitas ao cirurgião-dentista.
Mother's knowledge on oral health promotion for babies
Keywords: Oral health; Primary health care; Infant care; Saúde bucal; Atenção primária à saúde; Cuidado do lactente